(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
During the time of COVID-19 outbreak there is dilemma in diagnosis of acute lung infections. This is further hindered among immunocompromised patients due to bizarre clinical and radiological findings. We report young male severely immunocompromised HIV infected ART naïve patient presenting with acute onset of pneumonia and hypoxemia with SARS CoV-2 PCR positive.